Environmental Sustainability in Developing Countries: Does Democracy Matter? - Ursavaş, Neslihan; Apaydın, Şükrü (Problemy Ekorozwoju, 2024)
One of the sustainable development goals is to reduce environmental degradation and promote a sustainable environment. One of the significant factors in promoting a sustainable environment is the level of democracy in a country. This study investigates the impact of democracy on the ecological footprint (EF) per capita in 68 developing countries from 1990 to 2018. To do so, we use the Feasible Generalized Least Squares (FGLS) and Panel Corrected Standard Errors (PCSE) estimators. The empirical findings show that there is a positive relationship between democracy and EF. In other words, an increase in democracy increases environmental degradation in developing countries. Besides, the findings also show that while an increase in GDP per capita increases EF, an increase in renewable energy consumption reduces EF. Overall, our findings show that democracy matters for environmental sustainability in developing countries. Therefore, governments and policymakers should consider democracy to formulate environmental policies.